Investigate the Effects of Iranian Traditional Music and Western Classical Music on Physical Performance, the Normal Profile of Mood States and Rate of Perceived Exertion - Azam 1, Kamal; Entezari zarch 2*, Elham; Zakerian 3, Seyed Abolfazl (Shahroud Journal of Medical Sciences, 2017)
Background: The present study examines the effects of Iranian traditional music and Western classical music during 20 min of pedaling on an ergometer, along with the normal factors of profile of mood states and rate of perceived exertion. Methods: Seventeen non-athlete participants (11 men and six women) with a mean age of 26±1.5 cycled in three conditions: exposure to Iranian traditional music; exposure to classical music; and control conditions (silence). Participant’s normal mood states before and after each test, rate of perceived exertion and cycling speed during the test and distance traveled at the end of each test were recorded.Results: The results showed that participants in exposure to classical music, and also in the face of Iranian traditional music, pedal a greater distance than the control condition (silence). Also, conditions of exposure to classical music and exposure to Iranian traditional music reduced rate of perceived exertion of participants compared to control conditions (silence). There was no significant difference in the speed of participant’s cycling during exposure to music and in the control condition (silence). Conclusions: Individual’s mood during the physical test under the musical conditions was better than control condition, and classical music had a more prominent role in participant’s mood.